2017
DOI: 10.1002/jcp.25625
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Training Leads to Hepatic Fat Accumulation

Abstract: Recently, we demonstrated that an overtraining (OT) protocol for mice based on downhill running sessions increased the hepatic phosphorylation of 70-kDa ribosomal protein S6 kinase 1 (S6K1; Thr389), a downstream target of the mammalian target of rapamycin complex 1 (mTORC1). In liver, the overactivation of the Akt/mTORC1 pathway induces lipogenesis via regulation of the action of sterol regulatory element binding protein-1 (SREBP-1) at multiple steps. Herein, we verified the effects of three running OT models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…The slices were stained with hematoxylin for 10 min or with oil red O solution (Sigma-Aldrich) for 25 min, washed and stained with eosin (5 min). The slices stained with oil red O were used to analyses of lipid droplets area and red stained area using ImageJ (Schneider et al 2012) program using the 40× image, in agreement with previous studies (Botezelli et al 2016, da Rocha et al 2017, Muñoz et al 2018).…”
Section: Liver Hematoxylin-eosin Histology and Oil Red O Stainingmentioning
confidence: 78%
“…The slices were stained with hematoxylin for 10 min or with oil red O solution (Sigma-Aldrich) for 25 min, washed and stained with eosin (5 min). The slices stained with oil red O were used to analyses of lipid droplets area and red stained area using ImageJ (Schneider et al 2012) program using the 40× image, in agreement with previous studies (Botezelli et al 2016, da Rocha et al 2017, Muñoz et al 2018).…”
Section: Liver Hematoxylin-eosin Histology and Oil Red O Stainingmentioning
confidence: 78%
“…Recently, our research group showed that mice subjected to a downhill running–based overtraining (OTR/down) protocol presented elevated levels of proinflammatory cytokines in the serum, hypothalamus, muscle, and liver (da Rocha, Pinto, et al, ; Pereira et al, ). Also, this OTR/down model induces the nonfunctional overreaching (NFOR) state (da Rocha et al, , ), which is defined as a performance decrement or stagnation that may be reversed after weeks/months of recovery (Meeusen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As soon as anesthesia was confirmed by the loss of the pedal reflexes, the abdominal cavity was opened, the portal vein was exposed, and saline with and without human recombinant insulin (10 U.kg -1 , Eli Lilly, Indianapolis, IN) was injected. At 90 s after saline or saline with human recombinant insulin injection (Pauli et al 2008, Ropelle et al 2006, gastrocnemius samples were removed and used for immunoblotting analysis as previously described (da Rocha et al 2015, da Rocha et al 2016a, da Rocha et al 2017, Pereira et al 2015a, Pereira et al 2015b, Pereira et al 2014a, Pereira et al 2014b. Herein, we used the following antibodies: beta-actin (SC69879), GLUT-4 (SC53566) and PGC-1α (SC13067) from Santa Cruz Biotechnology (Santa Cruz, CA, USA) at dilution of 1:750; Akt (CELL9272S), phospho-Akt (Ser473; CELL4058S), AMPKα (CELL2532S), phospho(p)-AMPKα (Thr172; CELL2535S) and GLUT-1 (CELL12939S) from Cell Signaling Technology (Beverly, MA, USA) at dilution of 1:1,000.…”
Section: Methodsmentioning
confidence: 99%